Typing Dynamics Biometric Authentication through Fuzzy Logic - Zhe, Jin; Andrew Beng Jin, Teoh; Thian Song, Ong; Connie, Tee (2008)
The request to protect sensitive data and computer systems from malicious impostors while allowing ease of access for legitimate users is one of the greatest challenges in the computer security field. Traditionally, conventional ID and passwords authentication schemes are used for controlling access to computer systems. However, this approach has many inherent flaws such as password sharing and password guessing. To confront these problems, we propose a dynamic typing biometric authentication method for computer security system. As a user's typing template cannot be shared, lost or forgotten. It can be reliable used to gain access to the computer system. In this paper, we examine the behavioral biometrics of typing dynamics which uses the manner and rhythm in which an individual types characters on a keyboard or keypad. Experiment shows that an equal error rate (EER) of 20% could be achieved using the proposed approach. This paper focuses on the application of fuzzy logic in typing dynamic and explores the advantages of using this method as compare to the statistical standard deviation.